A 4D ATM Trajectory Concept Integrating GNSS and FMS?. (July 2014) - Brooker, Peter
<x content-type="archive" xml:space="preserve">Abstract</x> NextGen and SESAR have now been under development for several years, but have increasingly complex engineering and operational specifications. A variant Air Traffic Management (ATM) concept is sketched for generating fuel-efficient, very accurate and air-ground synchronized 4D-trajectories by using flight segment groundspeed profiles and linking Global Navigation Satellite Systems (GNSS) data to the aircraft Flight Management Systems (FMS) with feedback control. Is this a flawed concept or a feasible and operationally practical proposition?